Types of Works On Law On Intellectual and Artistic Works: A Comparative Analysis - Turan, Metin (Information World, 2014)
According to the Law On Intellectual and Artistic Works, work is any intellectual or artistic product bearing the characteristic of its author, which is deemed a scientific and literary or musical work or work of fine arts or cinematographic work. In this study, the Law On Intellectual and Artistic Works and the Copyright Laws of Spain, Germany, France and United Kingdom which are leading countries in this field are examined. This study where content analysis is used is limited to legal provisions related to the work and types of works and aims, in this context, to determine the conditions and problems of copyright law in Turkey. The hypothesis in this study is determined as, because Turkey, Spain, Germany, France and the United Kingdom have approved Berne Convention, Rome Convention, WIPO Copyright Treaty, WIPO Performances and Phonograms Treaty, Agreement on Trade Related Aspects of Intellectual Property Rights and the European Union (EU) Directives and brought them in to conformity with their legislations, there is no mismatch in their copyright legislations. As a result of the study, it is ensued that there is no mismatch in terms of work and types of work between the associated countries’ copyright legislations and, the hypothesis is proven.
Keywords: Law On Intellectual and Artistic Works; Copyright; Works; Types of works; Leading countries; International copyright agreements; Content analysis